A model for utilizing spillover taxes and community-based funds to fill the green energy financing gap in Asia - Naoyuki Yoshino; Farhad Taghizadeh-Hesary (Asian Development Bank Institute (ADBI), 2018)
In 2016, 88.90% of Asia and the Pacific's primary energy consumption was from fossil fuel, and almost 40% of the global CO2 emissions were from Asia and the Pacific. In order to ensure the increasing energy needs of the region are in line with sustainable development goals, addressing the financing gaps of green-energy projects is critical. The major challenge for filling the financing gaps of green energy is the lower rate of return on green projects compared to fossil fuels. Electricity tariffs are often regulated by governments. Electricity has to be kept low in price to serve every household as a necessary good. Green energy's sources of revenue are only from user charges. Hence, it is not so attractive to investors. This paper proposes a model for utilization of the tax revenue spillover from green-energy supply by returning a portion of the taxes to green-energy projects in order to increase their rate of return. In addition, the paper proposes a social community-based funding scheme for smaller-scale green projects (e.g., solar and wind). The paper theoretically shows that using this model for funding green-energy projects will increase the rate of return and make them feasible and interesting to private investors.
Keywords: Q21; E62; G21; 330; green energy; green finance; renewable energy; hometown investment trust funds; community-based fund; spillover effect